Stepped characterisation: a metaphysical defence of qua-propositions in Christology - Labooy, Guus (International journal for philosophy of religion, 2019)
Given Conciliar Christology and a compositionalist metaphysics of the incarnation, I explore whether 'qua-propositions' are capable of solving the coherence problem in Christology. I do this by probing the metaphysical aspect of qua-propositions, since 'semantics presupposes metaphysics' (McCord Adams). My proposal focuses on the fact that the Word accidentally owns an individual human nature. Due to that individuality, the human properties first characterise the individual human nature and, in a 'next step', this individual human nature characterises the Word. I call this 'stepped characterisation'. Subsequently, I show that stepped characterisation validates the use of qua-propositions in Conciliar Christology. Hence, qua-propositions are not merely 'muddling the waters of logic' (Morris).